Knowledge and Competences of the Green Technology Firms in Poland - Marczewska, Magdalena; Jaskanis, Adrianna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The article discusses the issue of the knowledge based competitive advantage of the Polish green technology firms. The purpose of the article is to identify knowledge sources and competences in terms of gaining new knowledge, which are the core of the market success of the researched companies. The research was conducted with the use of qualitative research methods – in‑depth interviews (IDI) and its results determined the sources of the knowledge and competences of the companies and their methods of forming. The results allowed to present the main knowledge and competence sources of the green technology firms in Poland which are structured into pillars: research and development, knowledge about the competition, clients and recipients, market and its potential changes, as well as foreign markets. The companies’ competences are identified in the article which are crucial to the mode of operation of the companies and their strategic goals achievement, such as new technology creation, perfecting of the technology, sales augmentation and market expansion.